(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
Responding by exclusion is a consistent pattern of behavior described as the tendency to select the undefined object, among other defined, to an undefined name. Since the relationship (object name) does not always hold after a trial, the aim of this study was to investigate the effect of presentation of the undefined object characteristics in learning. It was requested that participants (10 children 24-34 months) choose a toy to the word dictated, among a set (baseline with defined objects and words); then, were conducted exclusion and learning probes. Features of the undefined object was demonstrated before the probes in Condition CD and did not occur in Condition SD. Eight children accounted for exclusion in all probes; there was no difference in learning probes. The data suggest that the demonstration of the object’s features does not contribute to learning.